PERANCANGAN DAN IMPLEMENTASI SISTEM INFORMASI JASA PENITIPAN PAKET BERBASIS WEBSITE MENGGUNAKAN FRAMEWORK BOOTSTRAP (Studi Kasus Anbiya Jastip) - Luluk Suryani; Raditya Faisal Waliulu (Electro Luceat, 2021)
Anbiya Jastip is an individual business engaged in the service sector. This service provides storage and delivery of packages between islands using ships. The delivery process at Anbiya's custody service, where the customer sends the package directly or through the market place to the storage address in Surabaya, Jakarta or Makassar then all packages will be sent to Sorong City via ship expedition. In one delivery, Anbiya Jastip can get hundreds of packages. This ship storage service business is in great demand by customers because the shipping costs can be cheaper and there is no minimum weight of goods applied. Such a great opportunity to continue to develop in Anbiya Jastip is not supported by the system because the recording and tracking of goods is still done manually where some are handwritten and some are recorded using Microsoft Word. The system to find out shipping costs is also ineffective because customers have to download several images to find the name and service fees that must be paid. The emergence of new care services is also a challenge for Anbiya Jastip to continue to innovate. These problems encourage researchers to design and establish information systems as a medium for recording, tracking and calculating every transaction made as well as a media for promotion. The system will be made website-based with the Bootstrap framework so that it is dynamic when accessed via a desktop or smartphone. The prototype will be designed using the Rapid Applications Development (RAD) method and testing will be carried out using BlackBox Testing.